Pengembangan Media Video Pembuatan Macam-Macam Lipit pada Mata Pelajaran Dasar-Dasar Busana Kelas X Busana di SMKN 3 Pekanbaru - Lilmuttaqin, Badrul Aini; Suci, Puji Hujria (Lembaga Yasin AlSys, 2025)
The teaching of basic fashion at SMKN 3 Pekanbaru, particularly in the topic of pleat-making, still relies on traditional media such as PowerPoint presentations and sewn samples, resulting in suboptimal learning processes. This study aims to examine the validity and practicality of instructional videos for teaching various types of pleats to Grade X Fashion students at SMKN 3 Pekanbaru. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), excluding the evaluation stage. Data were collected through interviews, observations, and questionnaires, with instruments covering aspects of software engineering, instructional design, and visual communication. Validation results indicate that the video media are highly valid, with scores of 90% from media validators and 92% from material validators. Practicality testing yielded scores of 98% from teachers (highly practical) and 89% from students (highly practical). These findings confirm that the developed instructional video is both valid and practical for use in teaching the production of various types of pleats.